A New Hope in Immunotherapy for Malignant Gliomas: Adoptive T Cell Transfer Therapy - Dong-Sup Chung; Hye-Jin Shin; Yong-Kil Hong (Journal of Immunology Research)
Immunotherapy emerged as a promising therapeutic approach to highly incurable malignant gliomas due to tumor-specific cytotoxicity, minimal side effect, and a durable antitumor effect by memory T cells. But, antitumor activities of endogenously activated T cells induced by immunotherapy such as vaccination are not sufficient to control tumors because tumor-specific antigens may be self-antigens and tumors have immune evasion mechanisms to avoid immune surveillance system of host. Although recent clinical results from vaccine strategy for malignant gliomas are encouraging, these trials have some limitations, particularly their failure to expand tumor antigen-specific T cells reproducibly and effectively. An alternative strategy to overcome these limitations is adoptive T cell transfer therapy, in which tumor-specific T cells are expanded ex vivo rapidly and then transferred to patients. Moreover, enhanced biologic functions of T cells generated by genetic engineering and modified immunosuppressive microenvironment of host by homeostatic T cell expansion and/or elimination of immunosuppressive cells and molecules can induce more potent antitumor T cell responses and make this strategy hold promise in promoting a patient response for malignant glioma treatment. Here we will review the past and current progresses and discuss a new hope in adoptive T cell therapy for malignant gliomas.